New academics in the South African research-oriented academy: A critical review of challenges and support structures - Dominguez-Whitehead, Yasmine; Moosa, Moeniera (My University, 2014)
An explicit drive to increase research production at South African universities is apparent, but this drive also calls for the emergence of researchers who have traditionally been marginalised and underrepresented in the academy. Developing a new generation of productive researchers and intellectuals in South Africa, particularly those who are underrepresented in academia and who come from historically marginalised groups, is not only a pressing national concern, it is also an endeavour that is taken seriously by universities that value research production, transformation, and diversity. This paper is specifically concerned with the challenges faced by new academics who come from historically marginalised groups and groups which are underrepresented in academia, and thus particular attention is paid to black academics, academics from working-class backgrounds, and women in the academy. We specifically focus on concerns surrounding their success in the academy and in research production by addressing the transition from student to academic staff member, and the appropriation of the language of the academy. We argue that fundamental changes are necessary to address the specified challenges, and thus call for adequate support structures that promote intentional socialisation into the academy; supportive networking practices, and non-hierarchical mentoring models.
Keywords: Black academics – research output – South Africa; Research production – South Africa; New academics – support structures – South Africa; Academic language